(untitled) (Orkopata. Revista de Lingüística, Literatura y Arte, 2022)
The research reported here seeks to investigate, interpret and understand first-hand, how to develop reading skills for hypertext texts, in a group of twenty eighth grade students through a qualitative methodology with an epistemological approach in accordance with the case study method. As a result, a hypertext reading skill known as integration of hypertext texts and some guidelines that can be applied in a school context were tracked.